Engaging Canadian First Nations women in cervical screening through education. Issue 5 (2nd September 2016) - Zehbe, Ingeborg; Wakewich, Pamela; Wood, Brianne; Sameshima, Pauline; Banning, Yvonne; Little, Julian; ,
Abstract : Recognition of the need to decrease cervical cancer rates in Indigenous populations has been ongoing – yet few successful interventions have been reported. In addition, the literature addressing the challenges and barriers associated with designing screening programs aimed to specifically reach Indigenous women is limited. Here, we report findings from a mixed methods cervical cancer research project conducted in partnership with 10 First Nations communities in Northwest Ontario, Canada. Individual interviews with community health professionals (the majority of whom identified as First Nation) stressed that awareness of cervical screening benefits is lacking. In contrast, focus group participants (women with no formal health education) emphasized the desire to learn more about the science of human papillomavirus (HPV) and that a positive HPV or abnormal Papanicolaou test need not mean a woman will develop cervical cancer. Both the health professionals and the focus group participants highlighted that sexual health education must start early, in schools, preferably before girls are sexually active and that it has to continue throughout life to create a screening culture with a focus on women's well-being. Health professionals elaborated mainly on special events for community women, whereas focus group participants also recognized the need to include community men in health education particularly for destigmatizing the sexually transmitted HPV infection.